Russia vs America cyber war: space technology mastery competition - Fadra, Fadra; Santoso, Joseph Teguh (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
Mastery of computers and information systems in international relations is one of the elements of a country's new power. In the context of cyber warfare, Russia and the United States are trying to modernize their technology to secure their countries in the event of an attack from the opposing party. This research aims to analyze the space technology competition carried out by two major countries, namely Russia and the United States, to achieve Great Power status in the international world. This research focuses on the technological achievements of Russia and the United States in the field of space and their implementation in the form of cyber warfare. A qualitative case study is the research method chosen by the researcher. The research stages used by researchers are divided into data collection stages and data reduction, and the next stage is that researchers conduct analysis using data reduction techniques, namely summarizing, selecting, and focusing on the things needed in this study. The results of this study show that national security priorities are number one, and especially defense priorities for the United States are no longer terrorism but great power competition. NATO is an alliance or political tool that the US relies on to achieve great power.